Multiple Debris Flows as Emerging Threat to Dam Safety in Malaysia - Taher T.M.; Omar R.C.; Jaapar A.R.; Aripin M.F.S.M.; Wahab W.A.; Roslan R.; Zarime N.A.; Solemon B.; Isa A.A.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Debris flow is one of the most dangerous geo-disasters that can endanger lives and causes loss of property. A multiple debris flow consists of two or more surges of debris flows. In this study, we aimed to introduce/assess the formation and impact of debris flow. Then, its potential threats towards dam safety were associated. Several factors were considered in assessing debris flow such as geology and geomorphology, precipitation, erosion and siltation, and land use. The phenomenon started from landslide at the water divide zone that flows into the river channel that carried large debris (rocks, tree, and boulders) to the downstream. Constant flowing of high volume of water resulted in mud flood due to the muddy fluid from the debris. The whole downstream area is potentially at high risk. The impact of this phenomenon is highly risky for critical infrastructure such as the hydropower dam. Thus, these studies are of great significance in understanding the consequences of landslide warning in the future. In the perspective of dam safety, mitigation should be planned early to prevent damage and preserve the renewable energy source. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.